On large indecomposable modules, endo-wild representation type and right pure semisimple rings - Simson, D. (Algebra and Discrete Mathematics, 2003)
The existence of large indecomposable right Rmodules over a right artinian ring R is discussed in connection with the pure semisimplicity problem and the endo-wildness of the category Mod(R) of right R-modules. Some conjectures and open problems are presented.